2022
DOI: 10.1002/ejp.1916
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory role of nitric oxide in morphine‐induced analgesia in the descending path of pain from the dorsal hippocampus to the dorsolateral periaqueductal gray

Abstract: Background: Nitric oxide (NO) levels in brain nuclei, such as the hippocampus and brainstem, are involved in morphine analgesia, but the relationship between the dorsal hippocampus (dH) and the dorsolateral periaqueductal gray matter (dlPAG) needs to be clarified, which is our goal.Methods: Wistar rats were simultaneously equipped with a stereotaxic device with unilateral guide cannula at dH and dlPAG. After recovery, they were divided into control and experimental groups. Formalin (50 μl of 2.5%) was inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…An inducible NO synthase (NOS2, ENSG00000007171) was downregulated at the transcript level (–2.5 log-fold change; p = 3.36 × 10 −6 ). NOS2 generates NO, a messenger molecule with diverse functions in multiple human tissues [ 43 , 44 , 45 ]. Transcription of the arginine synthase ARG2 was also downregulated ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…An inducible NO synthase (NOS2, ENSG00000007171) was downregulated at the transcript level (–2.5 log-fold change; p = 3.36 × 10 −6 ). NOS2 generates NO, a messenger molecule with diverse functions in multiple human tissues [ 43 , 44 , 45 ]. Transcription of the arginine synthase ARG2 was also downregulated ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the increased nNOS expression induced by DEX, which suppressed nerve injury, is probably completed by suppressing the release of pain-related neurotransmitter of primary sensory neuron. 23 24 The diverse analgesia pathways of DEX can be performed by intravenous or intrathecal administration to improve postoperative effect. Also, its wide application range and safety allow DEX to be applied in various postoperative analgesia cases.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also have suggested that the analgesic effect of some painkillers is due to the activation of descending inhibitory pathways. As, a recent study ( Hashemi et al, 2022 ) has shown that high levels of NO in the dorsolateral periaqueductal gray (dlPAG) may regulate the pain process through downward synaptic interactions. The involvement of NO in both the dorsal hippocampus (dH) and dlPAG matter was observed in morphine-induced analgesia during the rat formalin test.…”
Section: Discussionmentioning
confidence: 99%